Принципи інтерактивного навчання студентів у закладах вищої освіти - Мілько, Дмитро Олександрович; Милько, Дмитрий Александрович; Milko, Dmytro; Педченко, Анна Павлівна; Педченко, Анна Павловна; Pedchenko, Anna; Педченко, Е. П. (ТДАТУ імені Дмитра Моторного, 2020)
UK: В статті розглянуто сутність та завдання інтерактивного навчання у закладах вищої освіти. Висвітлено основні дидактичні та методичні принципи інтерактивного навчання студентів вишу. Визначено позитивні наслідки інтерактивного навчання для суб’єктів вищої освіти. EN: The essence and tasks of interactive learning in higher education institutions are being considered in the article. The basic didactic and methodical principles of interactive teaching of students of the university are highlighted. Positive consequences of interactive learning for the subjects of higher education are determined.
Principles of interactive learning for student in higher education institutions
Keywords: інтерактивне навчання; заклади вищої освіти; дидактичні принципи; методичні принципи; interactive learning; higher education institutions; didactic principles; methodical principles